2018
DOI: 10.1002/kin.21151
|View full text |Cite
|
Sign up to set email alerts
|

Reaction Mechanisms and Kinetics of the Melt Transesterification of Bisphenol‐A and Diphenyl Carbonate

Abstract: The catalyzed and uncatalyzed reaction mechanisms of the melt transesterification process of bisphenol‐A and diphenyl carbonate are proposed based on nucleophilic substitution at the carbonyl group of the reactants. The reaction paths and energy barriers of the melt transesterification reaction were predicted and identified via density functional theory (DFT) calculations. The calculations reveal that the different oligomers with only one repeating unit are formed through different thermal processes. The theor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 29 publications
0
9
1
Order By: Relevance
“…75 Bases are also common catalysts, for instance magnesium hydroxide, 76 calcium salts 77,78 or sodium alkoxides. 74,79 All the catalyzed mechanisms described are associative, 69,71,74,[76][77][78][79][80] though they are slightly different depending on the type of catalysis employed (Scheme 3).…”
Section: Carbonatesmentioning
confidence: 99%
See 2 more Smart Citations
“…75 Bases are also common catalysts, for instance magnesium hydroxide, 76 calcium salts 77,78 or sodium alkoxides. 74,79 All the catalyzed mechanisms described are associative, 69,71,74,[76][77][78][79][80] though they are slightly different depending on the type of catalysis employed (Scheme 3).…”
Section: Carbonatesmentioning
confidence: 99%
“…The deprotonated counterpart (phenolate) is the reactive species toward the electrophilic carbon of the carbonate carbonyl moiety. The reaction proceeds through a tetrahedral intermediate before the elimination of a phenolate (from the starting carbonate or from the reactant). , However, this exchange is very slow . Transcarbonation is known to be catalyzed by metal-derived catalysts such as tin salts, zinc acetate, copper salts, and even a dimetallic iron–manganese cyanide catalyst .…”
Section: Exchangeable Bonds With An Associative Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous discussion, it was shown that the AMC‐catalyzed PC polycondensation system induces unfavorable branching structure related to the ability of the alkaline metal to bind several oxygen atoms simultaneously (see Section 3.1). For comparison, the QAH in Con‐A was considered as an efficient and steady catalyst to obtain high molecular weight PC with few side reactions 25,42 . Considering the larger ionic radius of QAH, and four phenyl groups increase the possibility of steric hindrance.…”
Section: Resultsmentioning
confidence: 99%
“…To produce a high molecular weight PC, it is necessary to add a suitable catalyst to the reaction system to improve its reaction rate. It has been reported that basic compounds such as alkali metals, 23 alkaline earth metals, 24 tetraethyl ammonium hydroxide 25 and others 26 show excellent catalytic performance in the synthesis of PC by melt transesterification process. However, little literature has been reported on the effect of catalysts for the MPP of PC.…”
Section: Introductionmentioning
confidence: 99%